Predicting the current and future distributions of Pinus merkusii in Southeast Asia under climate change - MUHAMMAD NUR SULTON; DEVI MAYANG AURINA; FARHAN MUHAMMAD; FARIZ PRADHANA ADIL FADZILAH; ZAHRA HANUN; MUHAMMAD INDRAWAN; SUGENG BUDIHARTA; JATNA SUPRIATNA; ILYAS NURSAMSI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Sulton MN, Aurina DM, Muhammad F, Fadzilah FPA, Hanun Z, Indrawan M, Budiharta S, Supriatna J, Nursamsi I, Setyawan AD. 2024. Predicting the current and future distributions of Pinus merkusii in Southeast Asia under climate change. Biodiversitas 25: 1135-1143. Pinus merkusii Jungh. Et de Vriese is a native pine species of Southeast Asia with primary distribution in Indonesia, especially in the mountainous areas of northern Sumatra. The P. merkusii has an important role in the forest ecosystem including maintaining ecosystem stability, reducing soil erosion, and providing habitat for various types of flora and fauna. Climate change is expected to affect the growth, development and distribution of plants, so this study aims to predicting the current dan future distribution of P. merkusii in Southeast Asia under climate change. We used Maxent and Geographic Information System (GIS), which incorporated bioclimatic, edaphic, and UVB radiation variables, to predict the suitable areas of P. merkusii under current and future climate scenarios (RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5) and three time periods (2030, 2050, and 2080). Our findings indicate that compared to current, there will be an increase of suitable areas for P. merkusii in 2030 across all climate scenarios with RCPs 2.6, 4.5, 6.0, and 8.5 represent 9.53%, 9.66%, 9.73%, and 9.91% of Southeast Asia terrestrial area, respectively. In 2050, such increase will continue under all climate scenarios with RCP 4.5 has the largest proportion of suitable area (10.39%). However, in 2080, the suitable areas are likely to reduce compared with 2050 with RCPs 2.6, 4.5, 6.0, and 8.5 have a percentage of 9.21%, 9.69%, 10.29%, and 9.81%, respectively. Our predictions showed that there will be a geographical shift of suitable area of P. merkusii into higher elevation and low latitude, migrating southeastward. Our findings about the potential future distribution of P. merkusii might be used as a reference for cultivation according to predicted suitable areas in the future.